Assessment of the optimal frequency of insecticide sprays required to manage fall armyworm (Spodoptera frugiperda J.E Smith) in maize (Zea mays L.) in northern Ghana - Jerry A. Nboyine; Ebenezer Asamani; Lakpo K. Agboyi; Iddrisu Yahaya; Francis Kusi; Gloria Adazebra; Benjamin K. Badii (CABI Agriculture and Bioscience)
Abstract Background Insecticide use is an important component of integrated pest management strategies developed for fall armyworm (FAW), Spodoptera frugiperda J.E Smith, control in maize in many African countries. Here, the optimum number of synthetic insecticide and biopesticide applications needed to effectively manage FAW at a minimal cost in maize was studied. Materials and methods A 3 × 4 factorial experiment arranged in a split plot design was used. Insecticides [Neem seed oil (NSO), 3% Azadirachtin); Emastar 112 EC (emamectin benzoate 48 g/L + acetamiprid 64 g/L); Eradicoat (282 g/L Maltodextrin)] were on the main plots, while insecticide spraying regimes [untreated control, spraying once (at VE–V5 maize develoment stage), twice (at VE–V5 and V6–V12 stages), thrice (at VE–V5, V6–V12 and V12–VT stages), four times (at VE–V5, V6–V12, V12–VT and R1–R3 stages)] were on the sub-plots. Results The results showed that larval infestations were generally lower in Emastar 112 EC treated maize than in those sprayed with Eradicoat or NSO. Infestations were higher in the untreated control (no spray) but decreased with increases in number of spray applications in insecticide treated plots. Again, crop damage was low in Emastar 112 EC treated maize. This variable also decreased with an increase in the number of spray applications. Grain yield was significantly affected by the spraying regime only, with this variable being lowest in the untreated control. In both years, yields were at least 1.5-fold higher in maize sprayed twice, thrice or four times compared to the untreated control. Emastar 112 EC had the highest net economic benefits. A single spray of Emastar 112 EC at the VE–V5 maize development stage resulted in maximum profits, while two sprays (i.e., at VE–V5 and V6–V12 stages) were needed for Eradicoat and NSO. Conclusion Hence, synthetic insecticides and biopesticides require different frequency of spray applications for cost effective management of FAW in northern Ghana. These findings are potentially applicable in other sub-Saharan African countries where this pest is present.